Frequency of anti-Leptospira sp. in sheep from the São João do Rio do Peixe microregion, Paraíba state, Brazil (Research, Society and Development, 2020)
Leptospirosis is an infectious disease that affects both domestic and wild animals, in addition to being an important zoonosis. In sheep farming it is mainly responsible for causing problems in the reproductive sphere, such as abortion, birth of weak and premature offspring, in addition to a drop in production. The sheep species is not refractory to the disease, and infected sheep can remain in the herd as amplifiers of the infection. Based on the lack of studies on the presence of the bacteria in the animals of the region, the present study aimed to verify the presence of anti-Leptospira sp. in sheep in the microregion of São João do Rio do Peixe, Paraíba state, Brazil. Blood samples were collected from 50 animals, and the experiment was conducted between December 2017 and February 2018. The diagnosis of leptospirosis was determined by the microagglutination test (MAT) technique, using a collection of 24 serological variants. The frequency found was 2% of the animals, all reactions occurred for the serogroup Pomona, which is normally maintained by the swine species. This transmission probably occurred due to the contact between species. The results found demonstrate the need to implement preventive measures, such as, for example, avoiding contact with pigs and their excreta, serological monitoring of herds, cleaning and disinfection of facilities and the use of personal protective equipment, especially for people working in direct contact with this species.